Daniel O'Rourke : an Irish tale - McDermott, Gerald (New York, N.Y., U.S.A. : Viking Kestrel, 1986)
Because of a pooka spirit, Daniel O'Rourke embarks on a fantastic journey.
Elem. School Library Collection
School Library Journal
Kirkus Review
3.8
K-3
Keywords: Folklore -- Ireland; Folklore -- Ireland